Worldly Conditions: The Society’s Response - Assawapoom, Phramaha Chuan Chawanaphanyo (Journal of Dhamma for Life, 2022)
This academic article aims to study worldly conditions in term of the society’s response. Today's society the ways of the world is considered to be the worldly Dharma that all human beings must experience. The life of people in modern times Buddhism has doctrinal principles and explanations about inherent worldly problems. Life experience teach human beings to accept the conditions and events that arise from all worldly things with oneself. These eight worldly things, on the one hand, will cause cravings, desires, and attempts to make them happen without limited scope. When they get it, they tend to become obsessed with forgetfulness and negligence. That is, when they have fortune, honor, praise, and happiness, they will become ignorant, arrogant and inflated. On the other hand, the worldly opposite, namely “Anitaram” is something that no person desires to happen to oneself because they want to experience happiness only. The Dhamma of the world are wealth, degradation, rank, degradation, praise, gossip, happiness and suffering. When the secular world of the undesirable nature comes into contact with the eyes, ears, nose, tongue, body, and mind, one will experience unwelcome suffering. If people trust to be neutral not obsessed with the mood of Lokadhamma will always be happy because today's society only needs the worldly morality. They have experienced happiness and chooses to reject the worldly nature because when experiencing it, there will be only physical and mental suffering. When people's denied the world of morality and adopted the secular world the mind becomes dull and weak. It is important to practice trusting according to the principle of impermanence, dukkha, and selflessness because it will make the minds of people in modern society a shelter when their minds experience the undesirable world of Dharma.